2020
DOI: 10.15578/squalen.v15i3.454
|View full text |Cite
|
Sign up to set email alerts
|

Design and Performance of Scaled-Up Microwave Dryer for Seaweed Drying

Abstract: Direct sunlight is commonly used to dry fresh seaweed by artisanal farmers in Indonesia due to its low cost and ease of handling. Nevertheless, this method poses some drawbacks such as lengthy duration, weather dependency and quality degradation. The application of microwave technology in food processing has progressed dramatically, including in the drying process. The microwave drying method is more efficient and can shorten the processing time. This study aimed to describe a large-scale microwave dryer (MD) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
0
1
0
1
Order By: Relevance
“…Rendemen minuman jahe merah K. alvarezii instan tiap perlakuan memiliki perbedaan yang nyata (p<0,05). Hal tersebut disebabkan oleh komponen penyusun K. alvarezii berupa air yang bersifat mudah menguap saat dipanaskan yaitu 80% b/b (Hakim et al, 2020).…”
Section: Hasil Dan Pembahasan Rendemenunclassified
“…Rendemen minuman jahe merah K. alvarezii instan tiap perlakuan memiliki perbedaan yang nyata (p<0,05). Hal tersebut disebabkan oleh komponen penyusun K. alvarezii berupa air yang bersifat mudah menguap saat dipanaskan yaitu 80% b/b (Hakim et al, 2020).…”
Section: Hasil Dan Pembahasan Rendemenunclassified
“…Dehghan-Manshadi et al (2020) evaluated the effect of spouted bed drying (SBD) on the properties of linseed oil at three temperatures, 40, 60, and 80 C. They found that the DR increases with increasing air temperatures. Altogether, fluidized and MW can be adjusted with the temperature parameters (air velocity and bed height for the fluidized bed and power density for the microwave) and moreover the moisture removal efficiency is greater than ambient air or sun drying (Hakim et al, 2020). Hence, it is important to seek the most effective method to improve the quality of substances envisaged for conservation or for their use as sources of useful constituents in the food, cosmetics, or pharmaceutical fields.…”
mentioning
confidence: 99%